The research methodology for malnutrition risk identification and dietary practices among community living elderly - Hamirudin, Aliza Haslinda; A. Rahman , Nor Azlina; Sidek, Suriati; Zainudin, Norain (IIUM Medical Journal Malaysia, 2016)
Introduction: Nutrition screening is an initial procedure to identify malnutrition, whilst subsequent nutrition intervention is warranted for at risk individuals. However, none of nutrition screening studies conducted among Malaysian elderly, accompanied by individualized nutrition intervention. The objective here is to describe the methodology to determine malnutrition risk and nutritional status of elderly in community at baseline and after 3 months of nutrition intervention; and to assess perception of elderly on their dietary practices. Methods: Elderly aged ≥ 60 years will be recruited as participants at several FELDA in Terengganu and Pahang with the calculated sample size of 416. Nutrition screening will be performed to identify malnutrition risk using a validated nutrition screening tool for the elderly in the community; the Mini Nutritional Assessment-Short Form. Dietary intake will be assessed using the diet history method and individualized nutrition intervention will be provided to improve nutritional status. Nutrition screening and assessment will be repeated after three months for malnourished and at risk elderly. An in-depth individual interview will be conducted to assess perception on dietary practices particularly prophetic food intake. Quantitative and qualitative data will be analyzed using IBM SPSS software and NVivo software, respectively. Results: Nutritional status of the elderly is anticipated to improve after 3 months of nutrition intervention and the elderly will perceive that their dietary practices are good. Conclusions: This research is at the forefront to provide individualized nutrition intervention following nutrition screening among Malaysian community elderly. It can potentially prevent further health complications associated with malnutrition through timely malnutrition identification and nutrition intervention.